QATHI’ DAN ZHANNI MENURUT MASDAR FARID MAS’UDI - KHOLIDAH KHOLIDAH (IAIN Padangsidimpuan, 2016)
Masdar Farid Mas'udi is one of the thought-leaders of Islamic law in Indonesia is a liberal. This is evident from his thoughts on the concept qath'i and zhanni reconstruction as a basis of interpretation and legal discovery method. He changed the general view of ijtihad, during which only reach things that are zhanni and less attention the dimensions of qathi. By placing the maslahah as the principle of ijtihad, the old concept of qath'i zhanni reconstructed to have a power on giving and solving various problems. Accordingly, the value of qathi is welfare and the justice system itself which is the spirit of the law itself, it can not be changed and not be a region of ijtihad. While zhanni category is the whole technical provisions or statutory normatively. The provisions of the law (normative) contained in the passage just a wasilah and will undergo changes, though not to be changed. Masdar’s thinking about the concept qath'i zhanni in turn, has changed the legal provisions because they are deemed no longer fit to the needs. Among the legal reasoning is, of zakat and taxes are also issues of women's reproductive rights. Thought zakat (tax) and also about the reproductive rights of women offered by Masdar is based on the principle of benefit-based justice. According to him, a double duty (pay zakat once taxes) inflicted on Muslims require that the concept of classical zakat should be revised. Similarly, the reproductive rights of women. Emasculation, inferior, and the subordination of women in all aspects of life should be terminated by giving a new meaning to the interpretation and nas